Pentingnya Pemadanan NIK – NPWP Bagi Wajib Pajak Orang Pribadi Serta Tata Cara Validasinya - Tjandra Wasesa; Heri Toni Hendro Pranoto; Diana Zuhroh; Sutini Sutini; Wiratna Wiratna (AKUNTANSI 45, 2023)
Taxes are the highest contributor to state revenue in the State Revenue and Expenditure Budget. This cannot be separated from the role of taxpayers' awareness in fulfilling their tax obligations, including making timely and annual tax payments and reporting. However, in practice, there are still many taxpayers who experience difficulties in carrying out their tax obligations. Taxpayers who find it difficult to report taxes electronically are directed to fill in the Annual Personal Income Tax Return and match the NIK-NPWP. One of the DJP programs for 2023, namely matching NIK and NPWP, is a national policy in the context of integrating population and taxation data. This new breakthrough is expected to make it easier for taxpayers in tax administration by only using NIK as a substitute for NPWP.The government again reminds Taxpayers to match their Population Identification Number (NIK) and Taxpayer Identification Number (NPWP) before 31 December 2023. This is because if the matching has not been carried out and the NIK and/or NPWP data is invalid, then the Taxpayer will not can access the services provided by the Directorate General of Taxes (DJP) on DJP Online.For this reason, taxpayers are expected to be able to immediately match their NIK and NPWP before the deadline for using the 15-digit NPWP ends so that they can continue to use tax services at DJP Online which can help taxpayers fulfill their tax obligations more easily and efficiently.